Association between knowledge, attitude and practice (KAP) towards sugar-sweetened beverage (SSB), body mass index (BMI) and SSB intake among undergraduates’ medical students in University Sains Malaysia Health Campus, Kubang Kerian, Kelantan - Qi, Ng Mei (2021)
Sugar-sweetened beverages (SSB) are beverages that composed of caloric-containing sweeteners such as sucrose, high-fructose corn syrup or fruit juice concentrates that are added to the beverages. Globally, the consumption on sugar-sweetened beverages have been increased rapidly. The study aims to determine the association between knowledge, attitude and practice towards SSB, body mass index (BMI) and beverages consumption among undergraduates’ medical students. A cross-sectional study was conducted among 122 respondents from school of medical sciences, USM Health Campus from March to May 2021. A set of questionnaires were used to collect the data included socio-demographic background, self-reported anthropometric measurements and KAP towards SSB. The beverages intake in past month was accessed using BEVQ. Most subjects were Malay with age more than 21 years old and had monthly family income of more than RM 3,000. Majority of the respondents fall within normal BMI category (61.5%) with mean BMI at 22.33 ± 3.58 kg/m2. The result suggested that male subjects with age more than 21 years old and lower monthly family income were more likely to have higher BMI. The highest mean percentage score was 95.0% for attitude, followed by a mean percentage of 59.8% for knowledge and the lowest mean score of 47.6% was for practice. The results suggested that males were more likely to have better attitude (t=0.046, p=0.006) and practice (t=0.162, p=0.048) towards SSB than females The finding showed low prevalence of SSBs consumption with only 9.8% has a daily high SSB intake, in which sugar-sweetened coffee or tea (18.9%) was the most common beverages consumed. The study found out that there was no association between KAP on SSB with SSB intake (p>0.05). There was also no correlation between BMI with SSB intake (p>0.05). Further studies need to be conducted that to understand the determinants of SSB consumption especially during Covid-19 pandemic.